Perbedaan Variasi Suhu dan Lama Pemanasan Terhadap Angka Total Kuman Susu Murni Pada Pedagang Susu Hangat Di Wilayah Kecamatan Cimahi Utara - Yosephina Ardiani S; Ad Hadi (VISIKES: Jurnal Kesehatan Masyarakat, 2016)
Milk is a food that contains the main nutrient for human needs but also as a medium suitable for microorganisms to multiply both pathogenic and non-pathogenic. Milk that has been contaminated with pathogenic bacteria can cause illness if consumed. Good handling can suppress contamination of microorganisms, such as by heating. This study aims to determine differences in variations in temperature and prolonged heating of the total number of germs in the pure milk warm milk traders in the District of North Cimahi. The type of research is applicable to the two experimental heat treatment temperature is 65oC and 75oC for 30 minutes for 15 seconds. Its population is whole milk sold by merchants of warm milk in the District of North Cimahi. Milk samples were used for each treatment equal to 250 ml. Data were collected by observation and laboratory tests. Data were analyzed using T test dependent. The results of this study indicate that the total number of germs in the group before the heat treatment temperature ranges from 65oC for 30 minutes 2,17x103-3,23x106 colonies/ml and groups prior to heat treatment temperature ranges from 75oC for 15 seconds 2,97x103-3,29x106 colonies/ml while the total number of germs in the treatment group after heating for 30 minutes 65oC temperature range between 8x101-4,9x104 colonies/ml and the total number of germs in the group after heating for 15 seconds 75oC temperature range between 2x101-3,4x104 colonies/ml. Dependent T test results obtained by value P value of 0.005 (<95% Î±=0.05). Thus statistically significant difference between the temperature of 65oC for 30 minutes and the temperature of 75oC for 15 seconds to the total number of germs milk. Traders are advised to use warm milk variations in temperature and prolonged heating temperature of 75oC for 15 seconds by lowering the total number of germs on pure milk is greater.The recommendation is doing further research on the relationship between of the handling of milk and the total number of germs in milk.Keywords: temperature, time of heating, germs, milk